Consumption and Supply of Electricity on Economic Growth in South Africa: An Econometric Approach - Stungwa, Sanele; Hlongwane, Nyiko Worship; Daw, Olebogeng David (International Journal of Energy Economics and Policy, 2022)
This study investigates the relationship between electricity consumption and electricity supply on economic growth in South Africa for the period spanning from 1971 to 2014. The importance of this study is to reveal the short run and long run impact of electricity consumption and electricity supply on economic growth in South Africa. The study borrowed annual time series data from the World Bank online secondary source for the period from 1971 to 2014. Empirical results revealed a positive statistically significant short run relationship and a negative statistically insignificant long run relationship between electricity consumption and economic growth. The results further reveal that renewable electricity has a short run negative statistically significant and positive statistically significant long-run relationship with economic growth in South Africa. Based on empirical results, it can therefore be recommended that the policymakers should implement policies that promotes renewable electricity generation and evaluate policies on electricity consumption so that it can significantly boosts economic growth in the long run.